CVPR 2011 2011
DOI: 10.1109/cvpr.2011.5995706
|View full text |Cite
|
Sign up to set email alerts
|

The light-path less traveled

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For this reason, special calibration procedures are necessary. In [70] a fixed (and known) mirror geometry is assumed and an algorithm for pose recovery of the real camera that is based on scene point correspondences (without knowing their reflection level) is derived.…”
Section: Multiple Mirrors Multi-bouncementioning
confidence: 99%
“…For this reason, special calibration procedures are necessary. In [70] a fixed (and known) mirror geometry is assumed and an algorithm for pose recovery of the real camera that is based on scene point correspondences (without knowing their reflection level) is derived.…”
Section: Multiple Mirrors Multi-bouncementioning
confidence: 99%
“…Recently, it has been shown that the minimum and maximum distances between line segments are very effective in pruning the search space in correspondence problems [28]. Note that we can also use the minimum distance between two line segments in building the L2L feature.…”
Section: (A)mentioning
confidence: 99%
“…The pose estimation problem for a calibrated mirror geometry has recently been investigated by Ramalingam et al [18]. In contrast, we aim at determining the geometry of a room of mirrors in conjunction with the camera pose.…”
Section: Introductionmentioning
confidence: 99%